Quality of life of public health service dental hygienists in GoiaÃƒâ€¹Ã¢â‚¬Â nia, Brazil - MF Nunes (Journal compilation 2008 Blackwell Munksgaard, 2008)
The aim of this study was to assess quality of life (QoL) and related factors among dental hygienists. A crosssectional study was conducted in a sample of dental hygienists working in the public health service of GoiaË† nia, Central-West Region, Brazil, in 2004.